Monitoring Lake Levels From Space: Preliminary Analysis With SWOT - Nair, Akhilesh S.; Kumar, Nitish; Indu, J.; Vivek, B. (Frontiers in Water, 2021)
Lakes are an essential component of biogeochemical processes, and variations in lake level are regarded as indicators of climate change. For more than a decade, satellite altimetry has successfully monitored variation in water levels over inland seas, lakes, rivers and wetlands. Through altimetry, the surface water levels are measured at varying temporal scales depending on the orbit cycle of the satellite. The futuristic mission of Surface Water and Ocean Topography (SWOT) scheduled to be launched in year 2022 shall offer the spatial coverage and resolution suitable for water level estimation and volume calculation in small water bodies like lakes worldwide. With a radar interferometer in Ka-band, SWOT proposes to provide two dimensional maps of water heights at a temporal resolution of 21 days. This work assesses the potential of SWOT for monitoring water volumes over a case study lake by analyzing SWOT like synthetic data produced using SWOT simulator developed by the Centre National d’Etudes Spatiales (CNES). With SWOT relying on a novel technology, the first 2 months of this mission after launch shall focus on an extensive calibration and validation. First hand results of SWOT simulated water levels and volumes are presented over case study region in the tropical band namely the Pookode lake, in the ecologically fragile district of Wayanad, Kerala, India. It is the second-largest freshwater lake in Kerala that is being affected by anthropogenic activities, causing huge depletion in lake water storage in the last four decades. Our analysis indicated that the lake region is subjected to a rise in temperature of 0.018°C per year. We further assess the potential of remote sensing and SWOT data to monitor water storage of Pookode lake which is undergoing a rapid change. Results show that the proxy water surface elevations have immense potential in scientific studies pertaining to lake monitoring across the world. Overall, the study shows potential of SWOT for monitoring the variability of water levels and volumes in this region.